2019
DOI: 10.1194/jlr.m094128
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of ANGPTL4 function in macrophages and adipocytes using Angptl4-knockout and Angptl4-hypomorphic mice

Abstract: Elevated plasma triglyceride levels are increasingly considered as an independent risk factor for cardiovascular diseases (1-3). Triglycerides circulate in the blood in two major forms: as chylomicrons carrying the dietary triglycerides and as very low density lipoproteins carrying endogenously produced triglycerides (4). The clearance of plasma triglycerides is primarily mediated by the action of LPL. This secretory enzyme is produced by parenchymal cells of fat tissue, skeletal muscle, and heart, as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 54 publications
4
41
1
1
Order By: Relevance
“…Growth factor in early stages of wound healing. Promotes dermal repair, angiogenesis and is expressed by anti-inflammatory macrophages 73 , 74 7.8 129.2 angptl4 Angiopoietin-like 4 00035942 00049924 4.1 3.9 Downregulated by TLR-stimulation in macrophages, prevents the formation of lipid-laden giant cells 75 and associated with anti-inflammatory macrophages 76 , 77 20.1 20.6 260.6 244.3 steap4 Six-transmembrane epithelial antigen of prostate 4 00042005 3.8 Metalloreductase involved in the transfer of ions from Fe 3 + and Cu 2 + to NAD and plays a role in cellular homeostasis during inflammation. Increased Steap4 may reduce circulating iron available for parasites 27 6.8 100.6 ppap2b or plpp3 Phosphatidic acid phosphatase type 2B/ Phospholipid phosphatase 3 00003642 00045370 3.8 3.7 Lysophosphatidic acid (LPA) inhibitor.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Growth factor in early stages of wound healing. Promotes dermal repair, angiogenesis and is expressed by anti-inflammatory macrophages 73 , 74 7.8 129.2 angptl4 Angiopoietin-like 4 00035942 00049924 4.1 3.9 Downregulated by TLR-stimulation in macrophages, prevents the formation of lipid-laden giant cells 75 and associated with anti-inflammatory macrophages 76 , 77 20.1 20.6 260.6 244.3 steap4 Six-transmembrane epithelial antigen of prostate 4 00042005 3.8 Metalloreductase involved in the transfer of ions from Fe 3 + and Cu 2 + to NAD and plays a role in cellular homeostasis during inflammation. Increased Steap4 may reduce circulating iron available for parasites 27 6.8 100.6 ppap2b or plpp3 Phosphatidic acid phosphatase type 2B/ Phospholipid phosphatase 3 00003642 00045370 3.8 3.7 Lysophosphatidic acid (LPA) inhibitor.…”
Section: Resultsmentioning
confidence: 99%
“…Data are of n = 3 fish. 1 Mills et al, 2000, 28 Mazzon et al, 2012, 52 Chen et al, 2001, 53 Chen and Lau, 2009, 54 Orecchioni et al, 2019, 55 Martinez and Gordon, 2014, 56 Nadella et al, 2015, 57 Sun and Kaartinen., 2018, 58 McLatchie et al, 1998, 59 Chen et al, 2011, 60 Pang et al, 2013, 61 Rogers et al, 2017, 62 Chen et al, 2019, 63 Broz et al, 2019, 64 Munder et al, 1999, 65 Jin et al, 2005, 66 Hertz et al, 2009, 67 Yang et al, 2017, 68 Stockmann et al, 2011, 69 Roszer et al, 2015, 70 Espina et al, 2013, 71 Das et al, 2018, 72 Eichelbaum and Krijgsveld, 2014, 26 Mantovani et al, 2019, 73 Shirakata et al, 2005, 74 Edwards et al, 2009, 75 Oteng et al, 2019, 76 Feingold et al, 2009, 77 Cho et al, 2019, 27 Scarl et al, 2017, 78 Wary and Humtsoe 2005, 79 Gustafsson et al, 2008, 80 Panchatcharam et al, 2014, 40 Carmans et al, 2010, 41 Loomis et al, 2019, 81 Della Fazia et al, 1997, 51 Ahmed and Prigent, 2017.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possible pathway mediating HDL-A-I atheroprotective function can be by raised expression of angiopoietin like-4 (ANGPTL-4), a known inhibitor of lipoprotein lipase [57] in endothelial cells: ANGPTL-4 reduces lipid uptake in macrophages [58]. By evaluating gene expression in whole genome microarrays, raised expression of ANGPTL-4 in EA-HY926 endothelial cells was found as one of the most up-regulated and biologically relevant molecules [59].…”
Section: Hdlthe Present Day Biologymentioning
confidence: 99%
“…In addition, the WC and waist-to-hip ratio is increased in adipocyte ANGPTL4 knockout mice [18]. Another research has found that the ANGPTL4 knockout mice fed with high-fat diet show granuloma lesions in intestine and WAT, as well as lymphangitis and mesenteric lymphadenitis [26,27], which suggests that ANGPTL4 is essential to the lymphatic drainage of lipids from WAT to the liver. A study has also reported that ANGPTL4 reduces appetite by inhibiting hypothalamic AMPK activity, accordingly, the ANGPTL4 knockout mice show increased appetite after fasting [28].…”
Section: Discussionmentioning
confidence: 99%